The Safety and Efficacy of the 1540nm Non-Ablative Fractional XD Probe of Star Lux 500 Device in the Treatment of Striae Alba: Before-After Study - Malekzad, Farhad; Shakoei, Safoura; Ayatollahi, Azin; Hejazi, Somayeh (Journal of Lasers in Medical Sciences, 2014)
Introduction: Striae distensae (SD) are a frequent skin condition for which treatment remains a challenge. The 1540-nm non-ablative fractional laser (Star Lux 500) has been shown to improve atrophic scars by increasing the amount of dermal collagen. To assess the safety and efficacy of the Star Lux 500 laser in the treatment of mature hypopigmented striae in Persian people (Striae Alba). Methods: Ten women aged 26–50 years with SD and Fitzpatrick skin types III–V were enrolled in the study. The exclusion criteria were a history of keloids, photosensitivity and collagen, elastin disorders as well as history of other striae treatment within one year. The lesions were treated with non-ablative fractional laser 1540nm, and a total of four treatments were given at 4-week intervals. Clinical standard photographs were taken before each treatment. Also, patients were followed up at 3 months after the last treatment. Clinical improvement was assessed by comparing baseline and post-treatment photographs by two independent blinded physicians using grading scale. Treatment efficacy analysis was performed via the comparison between the images taken before and after each treatment session. Results: There was a clinically appreciable improvement in striae ranging from 1 to 24%. A significant improvement in striae between the 16-week treatment and the 4-week treatment was identified (P<0.0001). Three months after the final treatment, patients showed noticeable improvement in the striae, compared with baseline (P<0.048). Mild post inflammatory hyperpigmentation was observed in one patient after the 8-week treatment and mild to moderate acne occurred in another patient after 4 weeks of treatment. Conclusion: Therapy with Star lux 500 laser had clinically and statistically striae improvement with no adverse events. This may be a safe and an effective treatment modality for Striae Alba lesions.